The Role of Social Media in Driving Community Innovation: A Mixed-Methods Study on Challenges and Opportunities in the Digital Age - Jap Caroline Valencia; Agus Wibowo (LPPM Politeknik Pratama, 2025)
Social media has increasingly become a driving force for community innovation in cyberspace. Platforms such as Facebook, WhatsApp, Instagram, and TikTok have empowered individuals and groups worldwide to collaborate, share ideas, and innovate collectively. However, despite these opportunities, social media also presents significant challenges, including misinformation, algorithmic bias, and issues surrounding trust and privacy. Utilizing a mixed- methods research approach, this study combines quantitative surveys and qualitative interviews to assess the impact of social media on community innovation. Data will be analyzed using descriptive statistics and thematic analysis to understand engagement, collaboration patterns, and the challenges faced by users. The study aims to contribute to existing research by providing insights into how social media platforms can be optimized for innovation and what strategies can be employed to overcome the digital divide and algorithmic biases. This study finds social media significantly enhances community innovation, with surveys indicating 95% faster collaboration, 100% idea generation efficiency, and 90% solution implementation post- adoption. Persistent challenges include misinformation (84% agreement), algorithmic bias limiting diversity (90%), and access gaps excluding marginalized groups (87%). Mixed- methods data reveal a paradox: platforms democratize innovation yet perpetuate inequities. Opportunities emerge in algorithmic transparency (80% agreement) and policy-driven digital inclusion (78%). Reforms prioritizing ethical governance, transparent AI, and inclusive infrastructure are critical to equitably harness social media’s potential as a global innovation catalyst.